Results of a prospective multicenter neuroendocrine tumor registry reporting on clinicopathologic characteristics of Greek patients. Issue 1 (December 2016) - Nikou, George; Pazaitou-Panayiotou, Kalliopi; Dimitroulopoulos, Dimitrios; Alexandrakis, Georgios; Papakostas, Pavlos; Vaslamatzis, Michalis; Kaldrymidis, Philippos; Markussis, Vyron; Koumarianou, Anna
Abstract Background The rare incidence of neuroendocrine neoplasms (NENs) has contributed to a paucity of large epidemiologic studies of patients with this condition. We investigated the occurrence and clinicopathologic features of NENs in Greece. Methods Between October 2010 and November 2012 we collected data on 246 newly diagnosed patients from a broad-based multi-institutional registry that comprises eight academic and hospital sites in Greece. The WHO 2010 pathologic classification and the 7th AJCC Staging system was applied in all cases. Results Of all patients 94 % had a sporadic and 6 % a multiple endocrine neoplasia tumor; 63.4 % were gastroenteropancreatic-(GEP)-NENs, 17.9 % Head & Neck NENs, 9.8 % NENs of Unknown Primary, 6.5 % Lung NENs and 2.4 % Pheochromocytomas. Gastric and pancreatic NENs were the most common primary sites. Poorly differentiated neuroendocrine carcinomas (NEC) were 9.3 %, all sporadic. Fifteen percent of patients were asymptomatic at presentation, 24 % had a first symptom of the disease related to endocrine syndrome and 61 % had symptoms related to locally advanced or metastatic disease. Metastatic disease was established in 25 % of tumors most frequently in the GEP NEN group. Findings are presented according to Ki-67 distribution. MRI had a higher diagnostic positive yield than Octreoscan. Somatostatin analogs, lanreotide and octreotide acetate, were prescribed at 38.5 & 61.5 % of NEN patients respectively and were found to be equally effective at providing symptomatic relief. Conclusions This is to our knowledge the first study of a Greek tumor registry and one of the few European Registries providing information regarding clinicopathologic characteristics and therapies in patients with neuroendocrine tumors of various origin sites, beyond GEP NENs.